The Social’s Life of Baduy Luar Tribe: An Observation - Wardatu, Adinda; Adzam, Fariz; Khadijah, Siti; Putria, Salwa; Afwan, Rizki; Faturrahmah; Mubarakh, Arya (Jurnal Ceteris Paribus, 2024)
The Baduy tribe is divided into two groups - the inner and outer Baduy tribes. The inner Baduy tribe has maintained their traditional way of life without any influence from modernization. In contrast, the outer Baduy tribe has started to interact with foreigners for research and tourism purposes, which has led to some modernization. However, their social life remains similar to that of the inner Baduy tribe. This study focuses on the social structure of the outer Baduy community, including marriage, customary laws, kinship, and community institutions. Qualitative research methods were used to collect data through observation and interviews. This research sheds light on the dynamics of the Baduy community.. Keywords: Outer Baduy, Social Structure of Baduy Community, Dynamics.